Synthesis of 4 Phenyl 3,4 Dihydr Indeno[2′,1′]Pyrimidine 2 One on Different Amount of Catalysts - Ritmaleni Ritmaleni; Megawati Parmasari (EKSAKTA: Journal of Sciences and Data Analysis, 2011)
Dihydropirimidine  is  a  heterocyclic  compound  which  has  important  pharmacologic  and  therapeutic  activities.  This  compound  can  be  synthesised  by  using Biginelli  reaction  which  involve  three  type  of  starting  materials  and  also  have  been developed  into  different method    of  reaction  condition  and  starting material.  LR1  (4phenyl3,4dihydroindeno[2′,1′]pyrimidine2one)  is  a  derivative  of  dihydropirimidine. This research was aimed to study the effect of catalyst amount in the synthesis of LR1 in order to reach the optimal yield.  LR1 can be synthesised form benzaldehyde, urea adn 2indanone in ethanol and concentrated chloric acid as catalyst for five hours under reflux. The product mixture was then  extracted  and  isolated  by  column  chromatography  preparative.  The melting  point was checked to determine the purity of the product. The structure elucidation was carried out by using spectroscopic method (uvvis, IR, 1HNMR and MS) The result showed that the highest yield of LR1 was obtained around 15 % when 0.25 %  of chloric acid used as catalyst. The higher the condition of acid in the reaction, the lower the tield of LR1 obtained.